PELAKSANAAN FUNGSI KELUARGA DALAM KELUARGA POLISI WANITA (POLWAN) DI LINGKUNGAN KEPOLISIAN DAERAH RIAU - Irfan Faturrakhman; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in the area of the Riau Provincial Police Unit. The purpose of this study was to determine the implementation of family functions in the family of female police (Polwan) in the Riau Regional Police Environment which reflected the family with the dual role of housewives and to find out the pattern of decision making of the female police (Polwan) family in the Riau Regional Police which reflected the existence of division of labor between husband and wife. Determination of informants by using purposive sampling method is the determination of samples based on certain criteria. The author uses qualitative methods with observation, interview and documentation techniques as well as literature studies to collect data and information. From the research conducted by the author, it can be concluded that from the family function, it is still run and implemented properly regularly and in balance with the others. These Policewomen are well aware of their nature as a wife who must be good at dividing time between work and household. Of the 8 family functions, only 6 functions are still carried out and implemented properly regularly and in balance with the others, namely the function of affection, socialization, determination of the status of sexual, reproductive and economic functions. while 2 other functions, namely: less protection and recreation, this is due to the busyness of respondents outside the home so that sexual and reproductive functions are not going well. Keywords: Family Function, Role of Decision Making, Female Police